Economic interventions to improve population health: a scoping study of systematic reviews - Mishal S. Khan; Bernie Y. Guan; Jananie Audimulam; Francisco Cervero Liceras; Richard J. Coker; Joanne Yoong (BMC, 2016)
Abstract Background Recognizing the close relationship between poverty and health, national program managers, policy-makers and donors are increasingly including economic interventions as part of their core strategies to improve population health. However, there is often confusion among stakeholders about the definitions and operational differences between distinct types of economic interventions and financial instruments, which can lead to important differences in interpretation and expectations. Methods We conducted a scoping study to define and clarify concepts underlying key economic interventions - price interventions (taxes and subsidies), income transfer programs, incentive programs, livelihood support programs and health-related financial services - and map the evidence currently available from systematic reviews. Results We identified 195 systematic reviews on economic interventions published between 2005 and July 2015. Overall, there was an increase in the number of reviews published after 2010. The majority of reviews focused on price interventions, income transfer programs and incentive programs, with much less evidence available from systematic reviews on livelihood support programs and health-related financial services. We also identified a lack of evidence on: health outcomes in low income countries; unintended or perverse outcomes; implementation challenges; scalability and cost-effectiveness of economic interventions. Conclusions We conclude that while more research is clearly needed to assess suitability and effectiveness of economic interventions in different contexts, before interventions are tested and further systematic reviews conducted, a consistent and accurate understanding of the fundamental differences in terminology and approaches is essential among researchers, public health policy makers and program planners.